The structural insight into the functional modulation of human anion exchanger 3 - Liyan Jian; Qing Zhang; Deqiang Yao; Qian Wang; Moxin Chen; Ying Xia; Shaobai Li; Yafeng Shen; Mi Cao; An Qin; Lin Li; Yu Cao (Nature Communications, 2024)
Abstract Anion exchanger 3 (AE3) is pivotal in regulating intracellular pH across excitable tissues, yet its structural intricacies and functional dynamics remain underexplored compared to other anion exchangers. This study unveils the structural insights into human AE3, including the cryo-electron microscopy structures for AE3 transmembrane domains (TMD) and a chimera combining AE3 N-terminal domain (NTD) with AE2 TMD (hAE3NTD2TMD). Our analyzes reveal a substrate binding site, an NTD-TMD interlock mechanism, and a preference for an outward-facing conformation. Unlike AE2, which has more robust acid-loading capabilities, AE3’s structure, including a less stable inward-facing conformation due to missing key NTD-TMD interactions, contributes to its moderated pH-modulating activity and increased sensitivity to the inhibitor DIDS. These structural differences underline AE3’s distinct functional roles in specific tissues and underscore the complex interplay between structural dynamics and functional specificity within the anion exchanger family, enhancing our understanding of the physiological and pathological roles of the anion exchanger family.